PENGARUH FORMALISASI PENGEMBANGAN SISTEM, KAPABILITAS TEKNIK PERSONAL, DAN KETERLIBATAN PEMAKAI DALAM PENGEMBANGAN SIA TERHADAP KINERJA SIA BERBASIS KOMPUTER PADA PERBANKAN DI BANDA ACEH - Ramadhan, Muhammad Kurniawan; Suazhari, Suazhari (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to examine the effect of formalizing system development, personal engineering capabilities, user involvement in developing Accounting Information System on the performance of accounting information systems. Testing used in this study is hypothesis testing. The data source used is primary data in the form of a questionnaire obtained from BUMN banking employees in Banda Aceh and analyzed using multiple linear regression methods. The sampling method used was random sampling with a population of 702 employees in state-owned banks in Banda Aceh, the sampling method uses the Slovin formula so that there are 88 samples in this study. The results of this study indicate that (1) the formalization of system development influences the performance of accounting information systems, (2) the capability of personal techniques influences the performance of accounting information systems, (3) the involvement of users in the development of AIS affects the performance of accounting information systems.